The Medium-Term Debt Management Strategy : An Assessment of Recent Capacity Building -- Annexes. (Policy Papers; Policy Paper ;, 2017)
This medium-term debt management strategy paper discusses the assessment of recent capacity building. The effective debt management and hence the design and implementation of a debt management strategy depend on the macroeconomic and institutional context, but the connection is two-way: sound debt management is critical to macro and financial stability, and financial and overall development. Within the constraints of the macroeconomic framework, the debt manager has the delicate task of balancing domestic and external sources of financing of various tenors to meet the government funding needs at low over-all cost and contained risk. Sound debt management contributes to reduced macro-financial risks, complementing prudent fiscal management and monetary policy implementation. Debt management contributes to market and institutional development. The debt manager's ability to cover external public financing requirements through external debt issuance and avoid undue bunching of debt service obligations helps reduce crowding out, exchange rate pressures, or large swings in international reserves.